Self-Introduction Training through Digital Marketing for Entrepreneurial Interest Development Among SMA Methodis Lubuk Pakam Students - Bambang Suwarno; Okta Jaya Hermanjaya; Feby Yoana Siregar (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This training program titled